2013
DOI: 10.1128/cvi.00625-12
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Functionally Oligoclonal Humanized Monoclonal Antibodies That Neutralize Clostridium difficile TcdA and TcdB with High Levels ofIn VitroPotency ShowsIn VivoProtection in a Hamster Infection Model

Abstract: Clostridium difficile infections are a major cause of antibiotic-associated diarrhea in hospital and care facility patients. In spite of the availability of effective antibiotic treatments, C. difficile infection (CDI) is still a major cause of patient suffering, death, and substantial health care costs. Clostridium difficile exerts its major pathological effects through the actions of two protein exotoxins, TcdA and TcdB, which bind to and disrupt gut tissue. Antibiotics target the infecting bacteria but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 61 publications
2
61
0
Order By: Relevance
“…In contrast, both actoxumab and bezlotoxumab are significantly less potent against strains of ribotypes 027, 036, 078 (toxinotypes III, X, and V, respectively), and 198 (unknown toxinotype). Shifts in potency for ribotypes 027 and 078 were reported by two other groups utilizing their own versions of actoxumab and bezlotoxumab (referred to in those studies as CDA1 and CDB1/MDX-1388, respectively) (20,21). In the study by Davies et al, the authors reported that CDA1 was "largely impotent" against TcdA from strains of ribotype 027 (20).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, both actoxumab and bezlotoxumab are significantly less potent against strains of ribotypes 027, 036, 078 (toxinotypes III, X, and V, respectively), and 198 (unknown toxinotype). Shifts in potency for ribotypes 027 and 078 were reported by two other groups utilizing their own versions of actoxumab and bezlotoxumab (referred to in those studies as CDA1 and CDB1/MDX-1388, respectively) (20,21). In the study by Davies et al, the authors reported that CDA1 was "largely impotent" against TcdA from strains of ribotype 027 (20).…”
Section: Discussionmentioning
confidence: 81%
“…To date, these conflicting findings have not been explained or resolved. Nonetheless, both toxins are lethal in animal challenge models, and antibodies against TcdA and TcdB can protect against disease (102). The fact remains that despite extensive study for more than 3 decades, the general roles of TcdA and TcdB in disease and their contributions to the overall virulence of C. difficile are not well understood.…”
Section: Factors Important To C Difficile Virulencementioning
confidence: 98%
“…In animal models, MAbs have been shown to reduce the severity and duration of diarrhea, death rate, and rate of recurrence [214] . Literature concerning the administration of a single MAb against either toxin A or toxin B seems to be conflicting; one early study reports that a MAb against toxin A was sufficient to protect form death, while a MAb against toxin B had no effect [215] .…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%